2021
DOI: 10.1039/d1ra06923c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of butadiene/isoprene–styrene di-block copolymer with high cis-1,4 unit content based on a neodymium phosphate ester

Abstract: A novel synthesis strategy of butadiene/isoprene–styrene di-block copolymer with high cis-1,4 content was explored based on a neodymium phosphate catalyst, by adjusting the electron cloud density of the catalytic active center via triphenyl phosphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…The similar 1 H and 13 C NMR spectra of copolymers in Table suggested their block microstructures but with different sequence lengths. DSC analyses showed that the copolymers had T g (−84.0 °C ∼ −86.8 °C) and T m (257 °C ∼ 270 °C), which were in accordance with the values for 1,4-enriched PBD homopolymers and crystallizable s PS . The close T g and T m of all the polymers with different sequence lengths further confirmed their block microstructures.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The similar 1 H and 13 C NMR spectra of copolymers in Table suggested their block microstructures but with different sequence lengths. DSC analyses showed that the copolymers had T g (−84.0 °C ∼ −86.8 °C) and T m (257 °C ∼ 270 °C), which were in accordance with the values for 1,4-enriched PBD homopolymers and crystallizable s PS . The close T g and T m of all the polymers with different sequence lengths further confirmed their block microstructures.…”
Section: Resultssupporting
confidence: 77%
“…In consideration of the structure-property relationship, it is believed that the introduction of certain regularity in both polystyrene and polybutadiene sequences will probably tailor the properties of resultant copolymers. As a milestone in polymer science, the coordination polymerization has obtained great successes in regio- and stereoselective polymerization of olefin and conjugated dienes, but only few catalytic systems based on titanium and rare-earth metal complexes could serve as dual catalysis for both styrene and butadiene polymerization with excellent selectivity. , The styrene–butadiene copolymers via coordination polymerization with diverse microstructures, such as diblocks and controlled sequences have been prepared, but the copolymerization always encountered low activity, low styrene incorporation, and so on. Therefore, the research on efficient copolymerization of styrene and butadiene with considerable regio- and stereoselectivity remained highly appreciated for preparing the copolymers with novel microstructures and properties.…”
Section: Introductionmentioning
confidence: 99%
“…These results show that the PS- b -PB copolymer contains high cis -1,4 unit content ( cis -1,4 > 95%) [ 19 ]. The 13 C NMR spectrum in figure 3 d shows chemical shifts at 27.4 ppm, 32.6 ppm, 34.2 ppm and 144.9–146.4 ppm corresponding to cis -1,4, trans -1,4, 1,2-, and PS microstructure, respectively [ 26 , 30 , 31 ]. These results demonstrate that the PS- b -PB copolymer is cis -1,4-regulated and isotactic-selective ( mmmm > 65%), which is consistent with the FT-IR results.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is difficult to obtain block copolymers with high styrene content. To solve this problem, Liu et al [26] used n-butyllithium to initiate styrene and obtain the macromolecular alkylation reagent PSLi, which was then combined with nickel naphthenate to achieve copolymerization with butadiene. However, the St block of the PS-b-PB obtained by this method presented atactic sequence, with extremely low stereoselectivity.…”
Section: Synthesis Of Styrene-butadiene Di-block Copolymer Using α-Di...mentioning
confidence: 99%